Assessment of Computer Task Performance for children: Standardization, validation and reliability. - Dumont, Claire; Mazer, Barbara (Technology & Disability, 2013)
The purpose of this study was to finalize the standardization of the Assessment of Computer Task Performance for children. Objectives were to obtain descriptive sample data for each age group from 5 to 10 years, identify factors associated with performance, and examine the inter-rater reliability, internal consistency and construct validity of the test in a sample of typically developing children (without impairments). The measure is composed of five standardized and timed keyboard tasks and five standardized and timed mouse tasks. The test was administered to a sample of 524 children recruited from schools and summer camps. Descriptive results for each age group are presented (mean, standard deviation, etc.) and factors associated with performance were identified. Thirty children underwent a second administration by a different evaluator to examine inter-rater reliability. Factors associated with performance were age, level of education and internet use; these factors are primarily associated with keyboard tasks. Gender and hand dominance were not associated with performance. The Assessment of Computer Task Performance for children has satisfactory metric characteristics and provides a standardized method of evaluating computer performance in young children. It may be used for various clinical and research purposes related to the use of the computer.